Activating Cannabinoid Receptor 2 Alleviates Pathogenesis of Experimental Autoimmune Encephalomyelitis Via Activation of Autophagy and Inhibiting NLRP3 Inflammasome. (December 2014) - Shao, Bo‐Zong; Wei, Wei; Ke, Ping; Xu, Zhe‐Qi; Zhou, Jv‐Xiang; Liu, Chong
Summary Aims Activation of cannabinoid receptor 2 (CB2R) has been reported to ameliorate the pathogenesis of experimental autoimmune encephalomyelitis (EAE). In this study, we examined whether autophagy is involved in the beneficial effect of CB2R on EAE and explored the mechanism with a focus on inflammasome activation. Methods EAE severity was analyzed with clinical score and histological score stained by hematoxylin and eosin or luxol fast blue in spinal cord. Immunoblot analysis was conducted to detect proteins of NOD‐like receptor family, pyrin domain containing 3 (NLRP3) inflammasome‐related caspase‐1 (Casp‐1) and the maturation of interleukin (IL)‐1β as well as autophagy‐related light chain 3 (LC3), and Beciln 1 both in vivo and in vitro. Reverse transcription and real‐time PCR were used to detect mRNA of NLRP3, IL‐1β and Casp‐1. Autophagy‐related gene 5 (ATG5)‐specific siRNA was transiently transfected in BV2 microglia, and immunofluorescence staining was carried out to detect the expression of NLRP3, caspase recruitment domain (ASC), and pro‐caspase‐1. Results The current data indicated that deleting CB2R decreased the expression of LC3‐II/LC3‐I ratio, Beclin 1 and increased caspase‐1 activation and IL‐1β production in the spinal cord of EAE mice, whereas activation of CB2R with a specific agonist HU‐308 induced inverse effects. Further study indicated that HU‐308 could promote autophagy and inhibit expression and activation of NLRP3 inflammasome in BV2 microglia. Blocking autophagy by ATG5‐specific siRNA dismissed the effort of CB2R in mediating NLRP3 inflammasome in vitro. Conclusion Collectively, our results demonstrated for the first time that CB2R plays a protective role in EAE through promoting autophagy and inhibiting NLRP3 inflammasome activation.